FRAILTY AMONG THE BENEFICIARIES OF BATUMI ST. CATHERINE NURSING HOME - Rusudan KHUKHUNAISHVILI (Rojan GÜMÜŞ, 2019)
Frailty is defined as "medical syndrome with multiple causes and contributors that is characterized by diminished strength, endurance, and reduced physiologic function that increases an individual's vulnerability for developing increased dependency and/or death. An assessment of Frailty in various populations, especially in the elderly population, has medical outcomes. The present work deals with the study of frailty in the beneficiaries of Batumi St. Catherine Nursing Home of. In total 70 beneficiaries of both sexes, were over 60 years of age, were investigated. Frailty phenotypes were assessed within five criteria: weight loss, self-reported exhaustion, weakness, slowness, and low physical activity (8). The existence of three and more criteria from these listed criteria are assessed as frail phenotype; the existence of one or two criteria - prefrail, and if a person does not have any criteria, it is assessed as robust. 25.7% of the elder beneficiaries turned out to be frailty phenotype, 12,9% - prefrail phenotype, 61.4% - healthy or sustainable. Total frailty phenotype was identified in 18 samples, including 11 women and 7 men. Hard cognitive disorders from the 18 frailty phenotypes were found in only 3 individuals. Among the three most commonly researched populations in the frailty criteria are low physical activity, weakness, and slowness. In the group of people older than 80 years, the syndrome of frailty was higher (35.7%) than in the group of people older than 60 years. (19%). The gender difference was not observed.